Improving cognition and perception towards failure: a conceptual replication study - Sinha, Tanmay (Frontiers in Psychology, 2025)
Despite its pedagogical value, failure is not often desired by students. To address this motivational barrier, I report a conceptual replication study that explored the synergistic effects of combining design principles from two distinct research traditions—growth mindset and utility value—to improve students’ dispositions toward failure. Using a single-group pre-post design, N = 68 lower secondary students from Singapore engaged in a pilot intervention involving prediction-explanation cycles on growth mindset myths along with evaluation of peer quotations reframing failure. Mixed methods analyses showed that this brief intervention was successful in significantly improving students’ learning goal orientation and attitude towards mistakes (strong effect sizes), representing rapid change in traditionally difficult-to-influence areas in education. Conversely, deeper cognitive orientations pertaining to beliefs about ability and the utility of failure showed non-significant improvements (weak to moderate effects). These results call on educators to proactively design repeated sense making opportunities involving reflections and vicarious learning to improve students’ cognition and perception regarding failure.